2017
DOI: 10.1002/lom3.10174
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods to estimate abundance and biomass from belt transect surveys

Abstract: It is becoming increasingly popular to use continuously collected acoustic or optical data to estimate abundance or biomass of fish and invertebrates. However, data from such systems are typically highly spatially autocorrelated and zero‐inflated, and thus simple design‐based estimation techniques are not applicable. Model‐based estimation methods can be used to extrapolate observations along the observed track to larger areas. We tested the precision and accuracy of three model‐based methods using both simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…In RK, the large-scale variation can be modeled using any type of regression which can be chosen based on the characteristics of the target simulated variables. For example, when the target variable is zero-inflated and over-dispersed, such as often the case for precipitation, two-stage hurdle regressions can be used (e.g., Chang et al, 2017;Zuur et al, 2009). A major advantage of RK is its ability to incorporate auxiliary information through covariates in the regression (Teutschbein & Seibert, 2012), so variables such as depth and month can be incorporated to inform the bias corrections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RK, the large-scale variation can be modeled using any type of regression which can be chosen based on the characteristics of the target simulated variables. For example, when the target variable is zero-inflated and over-dispersed, such as often the case for precipitation, two-stage hurdle regressions can be used (e.g., Chang et al, 2017;Zuur et al, 2009). A major advantage of RK is its ability to incorporate auxiliary information through covariates in the regression (Teutschbein & Seibert, 2012), so variables such as depth and month can be incorporated to inform the bias corrections.…”
Section: Discussionmentioning
confidence: 99%
“…RK is a spatial interpolation technique that models non-stationary trends using (generalized) regression, and then takes into account the spatial dependencies of the regression residuals using ordinary kriging (OK). RK has been used in a variety of disciplines and has proven effective in terms of modeling non-stationary and spatially autocorrelated objects (Chang et al, 2017;Hengl, 2009;Webster & Oliver, 2007). Unlike many bias correction methods that directly estimate the relationships between model-simulated output and observations, we use RK to estimate the "bias" across space and time.…”
mentioning
confidence: 99%
“…The non-stratified method consisted of an estimate based on the product of the mean abundance and the total area and the weight conversion factors for adults and juveniles. Design method estimations can be significantly improved by stratification (Chang et al 2017), so we introduced stratification based on depth (0-10, 11-20 and 21-30 m). The second design biomass was then calculated similar to the first method but for each stratum and then summed to obtain total biomass.…”
Section: Design Methods Biomass Estimationmentioning
confidence: 99%
“…From an ecosystem management standpoint, the risk of estimation errors is particularly problematic for density-dependent sedentary species such as the queen conch, in which allee effects can be enhanced by fishing leading to negative population growth and stock collapse (Stoner and Ray-Culp 2000). Chang et al (2017) suggested that predictions from design methods may be comparable to those from statistical models if the study area is accurately stratified. Accurate stratification can, however, be difficult or subjective and may contain large bias due to the unmodelled spatial autocorrelation from the spatial structure (Segurado et In this study, the best models were generally the GAMM and the ZINB based on the two evaluation statistics, MAE and RMSE.…”
Section: Spatial Model Performancementioning
confidence: 99%
“…The models were fitted by maximum likelihood to abundance trends and size data obtained from sea scallop dredge surveys during 1975-2019 (Serchuk andWigley, 1986, Hart andRago, 2006), drop camera surveys conducted in most years since 2003 (Stokesbury et al, 2004, Bethoney andStokesbury 2018), towed camera (Habcam) surveys during 2011-2019 (Howland et al 2006, Chang et al 2017 as well as commercial landings and shell height data from port samples and at-sea observers. Model estimates of survey efficiency were constrained by priors (likelihood penalties); the priors from the two optical surveys had an expected efficiency of one, whereas the expected efficiency of the survey dredge was based on paired tow experiments with Habcam (Miller et al 2019).…”
Section: Methodsmentioning
confidence: 99%